Abdominal obesity, adipokines and non-communicable diseases (2020)
Abdominal obesity may be defined as excess deposits of fat in the abdominal region. It is a common health condition seen in South Asians and is positively related to non-communicable diseases (NCDs). It is independent of body mass index and measured by raised waist circumference for men≥90cm and women≥80cm. The reason for its prevalence being common in Indians finds its root from pregnancy, during fetal period and has emerged as a concept of ‘Thin Fat Indian’. Malnutrition in such a critical period of growth has consequences in the form of educed basal metabolic rate (BMR), reduced blood flow to growing tissues, reduced functional ability of vital organs, endocrine changes and reduced capacity of primary adipose tissue. However, excess of visceral fat facilitates high dosage of adipokines in the portal vein to liver and other body tissues having serious implications seen in the form NCDs like diabetes, hypertension, heart diseases, non-alcoholic fatty liver diseases, kidney disorders, cancer and other health problems. Abdominal obesity should be addressed before it has progressed further to defined health issues by exercise and diet, so that people can live a quality life.